A novel ex vivo lung cancer model based on bioengineered rat lungs - Mizoguchi, Satoshi; Tsuchiya, Tomoshi; Doi, Ryoichiro; Obata, Tomohiro; Iwatake, Mayumi; Hashimoto, Shintaro; Matsumoto, Hirotaka; Yukawa, Hiroshi; Hayashi, Hiroko; Li, Tao-Sheng; Yamamoto, Kazuko; Matsumoto, Keitaro; et al. (Frontiers in Bioengineering and Biotechnology, 2023)
Two-dimensional cell cultures have contributed substantially to lung cancer research, but 3D cultures are gaining attention as a new, more efficient, and effective research model. Here, we describe the creation of a successful ex vivo lung cancer model based on bioengineered lungs formed by decellularization and recellularization. The model reproduces the 3D characteristics and tumor microenvironment of the lungs in vivo, including the coexistence of healthy alveolar cells with lung cancer cells. The morphology and MUC-1 expression of the model were like those of lung cancer in vivo. RNA sequencing revealed elevated expression of genes related to epithelial-mesenchymal transition, hypoxia, and TNF-α signaling via NF-κB; but suppression of cell cycle-related genes including E2F. Drug response assays showed gefitinib suppressed PC-9 cell proliferation equally well in the 3D lung cancer model as in 2D culture dishes, albeit over a smaller volume of cells, suggesting that fluctuations in gefitinib resistance genes such as JUN may affect drug sensitivity. Although this ex vivo lung cancer model was only evaluated for a short period, it closely reproduced the 3D structure and microenvironment of the actual lungs, highlighting its possible use as a platform for lung cancer research and pathophysiological studies.